Physicochemical and Biological Investigation of Different Structures of Carbon Coatings Deposited onto Polyurethane - Kaczorowski,Witold (2016)
The aim of this study was to examine the thrombogenic properties of polyurethane that was surface modified with carbon coatings. Physicochemical properties of manufactured coatings were investigated using transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray Photoelectron Spectroscopy (XPS), Raman spectroscopy and contact angle measurement methods. Samples were examined by the Impact-R method evaluating the level of platelets activation and adhesion of particular blood cell elements. The analysis of antimicrobial resistance against E. coli colonization and viability of endothelial cells showed that polyurethane modified with use of carbon layers constituted an interesting solution for biomedical application.